Corporate Social Responsibility, Company Value, and Company Size in Southeast Asia - Leni Yulianti; N Nugraha (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the relationship between company value and corporate social responsibility and company size. Method This research uses a quantitative methodology. Multiple regression analysis was used in the descriptive-verificative approach of the investigation. The research method used in this research is a quantitative approach companies served as the study's units of analysis. The research used a cross-sectional in Southeast Asia in 2022 which data is available at Thomson Reuters on the website https://www.refinitiv.com. The findings of this study showed that company value is positively impacted by corporate social responsibility while negatively impacted by company size. The findings of that study need for consideration by companies to implement policies related to corporate social responsibility and since it is a company size able to change investors’ views, therefore company goals are expected to include economic, environmental and social where the company is established. However, the companies also have to pay attention to the number and increase in total assets because high total assets a significant effect on high risk and competition. This study provides novel insights into the relationship between between corporate social responsibility and business value in the Southeast Asian region.